Plan estratégico para promover el micro emprendimiento de personas con discapacidad física en la parroquia San Juan - Espinoza Ponce, Daniela José (2019)
The present investigation is carried out with the purpose that people with physical disabilities of the San Juan parish can receive microenterprise talks and have jobs, they will also have the opportunity to be able to carry out those business ideas that have not developed them due to lack of help, not knowing how to propose a business plan and the lack of the respective financial analyzes. In Ecuador there are laws that protect, include and protect people with disabilities thanks to the timely intervention of national and international government. For this purpose, the raising and commercialization of topic chickens was taken as a reference, which was carefully analyzed by the surveys that were carried out in order to know the feasibility of the aforementioned topic for this purpose, the research line was used: Production and competitiveness, surveys, the NPV was applied, resulting in a $ 81,260.33, IRR of 39% and the RCB of 2.13, thus demonstrating the feasibility of implementing this idea